2007
DOI: 10.1073/pnas.0700257104
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal dynamics of human erythrocyte

Abstract: The human erythrocyte (red blood cell, RBC) demonstrates extraordinary ability to undergo reversible large deformation and fluidity. Such mechanical response cannot be consistently rationalized on the basis of fixed connectivity of the cell cytoskeleton that comprises the spectrin molecular network tethered to phospholipid membrane. Active topological remodeling of spectrin network has been postulated, although detailed models of such dynamic reorganization are presently unavailable. Here we present a coarsegr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
201
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 238 publications
(214 citation statements)
references
References 51 publications
6
201
0
1
Order By: Relevance
“…Theoretically, RBC membrane fluctuations were traditionally studied by using models of thermally-driven equilibrium systems (2, 3). A recent theoretical model (15,17), validated by simulation (18,19), showed that local breaking and reforming of the spectrin network can result in enhanced fluctuations. Our results here showed that the depletion of ATP decreased the fluctuations in RBC membranes that can be reversed when ATP is reintroduced.…”
Section: Atp Results In Non-equilibrium Dynamics For Membrane Fluctuamentioning
confidence: 99%
“…Theoretically, RBC membrane fluctuations were traditionally studied by using models of thermally-driven equilibrium systems (2, 3). A recent theoretical model (15,17), validated by simulation (18,19), showed that local breaking and reforming of the spectrin network can result in enhanced fluctuations. Our results here showed that the depletion of ATP decreased the fluctuations in RBC membranes that can be reversed when ATP is reintroduced.…”
Section: Atp Results In Non-equilibrium Dynamics For Membrane Fluctuamentioning
confidence: 99%
“…Melting of this layer resulted in a suspension of hydrogel particles. in fundamental structure: RBCs are fluid-filled sacs contained by a complex membrane that has extreme flexibility originating from the membrane structure (28,29), whereas the RBCMs are uninterrupted hydrogel discs. These two disparate structures should have different behaviors and mechanisms of deformation in constricted flow (13) though further studies are needed to elucidate these details for the RBCMs.…”
Section: Resultsmentioning
confidence: 99%
“…Microfludic device was used to induce large deformation of RBCs and its mechanical behavior was studied (Fig. 10) (Li, Lykotrafitis et al,2007) . For the study of sickle cell disease, microfluidic device has been used to measure the resistance change rate of blood flow under the sudden change of oxygen concentration (Wang, Ding et al,2011).…”
Section: Microfluidic Device Techniquementioning
confidence: 99%